If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 21 + -1z Solving 15 = 21 + -1z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add 'z' to each side of the equation. 15 + z = 21 + -1z + z Combine like terms: -1z + z = 0 15 + z = 21 + 0 15 + z = 21 Add '-15' to each side of the equation. 15 + -15 + z = 21 + -15 Combine like terms: 15 + -15 = 0 0 + z = 21 + -15 z = 21 + -15 Combine like terms: 21 + -15 = 6 z = 6 Simplifying z = 6
| 15f-34=56 | | (4/3)(0)-(3/4)g=52 | | x^2/7-78/7=-x | | y-15=3.5(x-0) | | x^2/7-78/7 | | y-15=7/2(x-0) | | k-79=8 | | (2x^-2y^3)^-2/-8x^-2y^2 | | 2x^2+8=80 | | 2x^2-8=80 | | 2x^2+8=-80 | | 4*5x=x | | .4b-.25=3 | | 3k^2+10=17k | | 20/x-12/x=9/(x-1) | | 19/4=38/X | | 2+10x=x-(-8) | | 20/x-12/x=9/x-1 | | 2x^3+14x-5=0 | | x-6/3=7 | | 22/2=77/M | | 8m-1=21 | | 2r+5=9 | | 6s^2=s | | M/16=784/28 | | T/12=81/9 | | 2c+3=4c-1 | | 3/4x5/4=-1/4 | | 4x-7=-3(3+4x) | | 7(x+6)+7(x+6)=5x-5 | | 4t-3=3t+7 | | 20/6=X/27 |